A scholar's path an anthology of classical Chinese poems and prose of Chen Qing Shan, a pioneer writer of Malayan-Singapore literature = [Qing shan gu dao] - Chen,Peter 1938- (IG library, 2010)
An original English translation from the Chinese text that comprises 60 poems (85 verses) and three prose compositions; Opens a window to the heart and mind of a Chinese scholar who lived from the late Qing through the 1950s; Reflects the life of a pioneer writer of Malayan-Singapore Chinese literature : his personal tragedies, struggles, disappointments and the joy in his family, friends and his poetry; English explanations for many interesting expressions and allusions used in Chinese classical poetry and; Enables an English language reader to enjoy the rich and colourful heritage of Chinese culture and language.